A Review Of The Management Theory For Special Education Task Load Perspective - et. al., Quah Wei Boon, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is evidence related to the existence of the issue of teacher workload through several studies. Many researchers have found that workload factors are closely related to the stress levels of special education teachers. They noted that this workload factor is also the highest factor that has caused stress among special education teachers. The study also found that the majority of respondents agreed that special education teachers are burdened with various tasks in school which will ultimately affect the quality of the teaching process and job satisfaction of the teachers involved. There are also studies that state that special education teachers not only need to carry out the teaching process in the classroom, but also be involved in administrative work, discipline management, substitute teachers and many other workloads. This situation requires special education teachers to manage their assignments efficiently and systematically. This study was conducted to examine the existing management theories, in helping teachers manage their assignments better.